ANALISIS PENDAPATAN USAHA TANI LEBAH TANPA SENGAT TRIGONA sp. DI DESA LALOPISI KECAMATAN MELUHU KABUPATEN KONAWE - Sarwinda Intan Putri; Rosmarlinasiah; Zakiah Uslinawaty; Niken Pujirahayu; Satya Agustina Laksannany; Abigael Kabe; Miselin Ratu (Jurusan Kehutanan -FHIL-UHO, 2025)
This study aims to analyze the income from stingless bee farming (Trigona sp.) in Lalopisi Village, Meluhu District, Konawe Regency. Data were collected through interviews with nine beekeepers involved in the honey farming business. The methodology includes field observations and quantitative analysis to calculate production costs, revenue, and annual income from honey harvesting. The results indicate that the majority of beekeepers are in their productive years (30-45 years old), with most having completed education up to junior high school level. The average annual production cost per beekeeper is IDR 6,125,000, with operational and equipment costs being the largest components. The annual revenue varies significantly among the beekeepers, with total revenue reaching IDR 38,580,000, but the average net income is only about IDR 3,606,111 per year per beekeeper. The study finds that honey production volume and managerial skills play a major role in determining income levels. Although the business shows promising potential, external factors such as climate change and bee colony health are major challenges. These findings imply that to improve beekeepers' income, more training and broader market access are essential. The sustainability of bee farming depends heavily on better management and supportive policies